Total Synthesis of Natural Terpenoids: Inspired but Not Limited by Biohypothesis - Chen, Juan; Liu, Bo (Synlett, 2018)
This account describes our studies on the total synthesis of several natural terpenoids based on our modified biosynthetic hypothesis. Compared to the originally proposed biosynthetic hypothesis, the modified ones proved to be more practicable for the formation of hispidanin A, a dimeric diterpenoid, and sarcandrolide J and shizukaol D, two dimeric sesquiterpenoids, from a viewpoint of chemical reactivity. Moreover, a cascade reaction involving intermolecular and intramolecular cycloaddition was facilitated to expeditiously accumulate molecular complexity in the total synthesis of bolivianine, a sesterterpenoid, on the basis of a modified biohypothesis.1 Introduction2 Total Synthesis of Hispidanin A3 Total Syntheses of Bolivianine and Isobolivianine4 Total Syntheses of Sarcandrolide J and Shizukaol D5 Conclusion
Keywords: terpenoids; total synthesis; biohypothesis; cascade; cycloaddition; cyclization